2007
DOI: 10.1007/s10461-007-9221-z
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Sex with Men among High-Risk, Heterosexually-Identified Men in Low-Income, Coastal Peru

Abstract: In this paper we describe sex with men, including the frequency of sex and unprotected sex, among high-risk, heterosexually-identified men in urban, low-income, coastal Peru. During 2001-2002, a random community-based sample of these men was administered an epidemiologic survey collecting sexual risk behavior data. Among the 924 high-risk heterosexually-identified men, 131 NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Author Manuscript (14.2%) reported at least one male partner in the past 6 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
(23 reference statements)
1
25
0
1
Order By: Relevance
“…Furthermore, these men are much more likely to only engage in insertive anal sex when they have sex with men. However, MSM who do not have sex with women are much more likely to engage exclusively in receptive anal intercourse (6, 6062). Given the higher efficiency of HIV transmission for receptive anal sex (63), insertive sex and sex with women are likely to be “protective” factors in the population of African MSM (8, 11, 57).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these men are much more likely to only engage in insertive anal sex when they have sex with men. However, MSM who do not have sex with women are much more likely to engage exclusively in receptive anal intercourse (6, 6062). Given the higher efficiency of HIV transmission for receptive anal sex (63), insertive sex and sex with women are likely to be “protective” factors in the population of African MSM (8, 11, 57).…”
Section: Discussionmentioning
confidence: 99%
“…Results on perception of risk for HIV also show a reversal of the usual concept of the ''bisexual bridge''. In the West, Asia, and Latin America, there has been concern that the high prevalence of HIV among MSM may cross into the low prevalence general heterosexual population through bisexual men to women (Choi et al 2003;Konda et al 2007;Prabhu et al 2004). Uganda, like many countries in East and Southern Africa, already has a generalized epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Other Peruvian studies have shown that people who use substances before sex are at particularly high risk of either having sex with another man, having unprotected sex with a casual partner, or having had an STD [16][17][18]. Similarly, heavy drinking significantly increases the risk of having multiple sexual partners, having had sex with a casual partner in the last year, and acquiring an STD [14,19,20].…”
Section: Overview Of Alcohol-illicit Drug Use and Associated Risky Bementioning
confidence: 96%